2001
DOI: 10.1007/bf02707598
|View full text |Cite
|
Sign up to set email alerts
|

On the empirical distribution of the Balassa index

Abstract: C14, F01,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(196 citation statements)
references
References 20 publications
5
157
1
11
Order By: Relevance
“…The first empirical test of the Hillman condition was executed by Marchese and de Simone (1989) by analysing exports of 118 developing countries at a different level of aggregation. They found that the Hillman condition does not hold for about 9.5% of the value of exports in their sample, while Hinloopen and Van Marrewijk (2001) proved that the Hillman condition does not hold for about half percent of the number of observations, which corresponds to about seven percent of the value of exports. According to the latest empirical tests, based on approximately 18 million observations coming from 183 countries and 28 years, violations of the Hillman condition are small as a share of the number of observations, but they often represent a disproportionally large value of trade (Hinloopen and van Marrewijk 2008).…”
Section: Methods and Data Usedmentioning
confidence: 94%
“…The first empirical test of the Hillman condition was executed by Marchese and de Simone (1989) by analysing exports of 118 developing countries at a different level of aggregation. They found that the Hillman condition does not hold for about 9.5% of the value of exports in their sample, while Hinloopen and Van Marrewijk (2001) proved that the Hillman condition does not hold for about half percent of the number of observations, which corresponds to about seven percent of the value of exports. According to the latest empirical tests, based on approximately 18 million observations coming from 183 countries and 28 years, violations of the Hillman condition are small as a share of the number of observations, but they often represent a disproportionally large value of trade (Hinloopen and van Marrewijk 2008).…”
Section: Methods and Data Usedmentioning
confidence: 94%
“…The results of the stability test as suggested by [13] are presented in Table 4 According to [15], changes in the distribution of the Balassa index provide information on the trend in a country's comparative advantage over time. The distribution of the Balassa index over the period [2004][2005][2006][2007][2008][2009][2010][2011] shows that Ghana's revealed comparative advantage in agro-processing products somewhat weakened over the period 2004 to 2011 ( Table 5).…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…See Hinloopen and Van Marrewijk's (2001) study on the empirical distribution of the Balassa index and the problem of the incomparability of RXA scores across countries.…”
Section: Discussionmentioning
confidence: 99%